Główne bariery w prowadzeniu edukacji tanatologicznej - Sobańska, Aleksandra (The main barriers to developing and implementing thanatological education(death education), 2024)
Research on thanatopedagogy – a subdiscipline of pedagogy related to education regarding the dying process and the complexity of biological, psychological, cultural- -social, philosophical, religious and ethical issues related to death – is constantly developing. The aim of the article is to identify the main barriers that may hinder the effective conduct of such education. They were distinguished on the basis of empirical research in July 2023, which involved over 140 Polish language teachers. The main research question was: what are the experiences of Polish language teachers in conducting thanatopedagogical education? Based on the answers obtained, five groups of barriers were distinguished that make it difficult to conduct effective thanatopedagogical education and relate to the teacher’s self-perception, students’ emotional reactions, the cultural taboo of death, educational influences undertaken by parents and the list of compulsory readings. The conclusions attempt to identify the sources of these barriers and present proposals for possible solutions to limit their impact.